Condition-Specific Competitive Effects of the Invasive Mosquito Aedes albopictus on the Resident Culex pipiens among Different Urban Container Habitats May Explain Their Coexistence in the Field - Paul T. Leisnham (MDPI AG, 2021)
Condition-specific competition, when environmental conditions alter the outcome of competition, can foster the persistence of resident species after the invasion of a competitively superior invader. We test whether condition-specific competition can facilitate the areawide persistence of the resident and principal West Nile virus vector mosquito Culex pipiens with the competitively superior invasive Aedes albopictus in water from different urban container habitats. (2) Methods: We tested the effects of manipulated numbers of A. albopictus on C. pipiens’ survival and development in water collected from common functional and discarded containers in Baltimore, MD, USA. The experiment was conducted with typical numbers of larvae found in field surveys of C. pipiens and A. albopictus and container water quality. (3) Results: We found increased densities of A. albopictus negatively affected the survivorship and development of C. pipiens in water from discarded containers but had little effect in water from functional containers. This finding was driven by water from trash cans, which allowed consistently higher C. pipiens’ survival and development and had greater mean ammonia and nitrate concentrations that can promote microbial food than other container types. (4) Conclusions: These results suggest that the contents of different urban containers alter the effects of invasive A. albopictus competition on resident C. pipiens, that trash cans, in particular, facilitate the persistence of C. pipiens, and that there could be implications for West Nile virus risk as a result.